Vegetarian Diet During Pregnancy: Making Sure Vitamin B12 Intake is Adequate. Issue 1 (January 2018) - Snow, Denise
Abstract : A well-planned vegetarian diet, including vegan, can be nutritionally sound with positive outcomes. However, failure to identify inadequacies of vitamin B12 can have serious results. Our expert on nutrition, Denise Snow, provides details on current recommendations to make sure women on a vegetarian diet get an adequate amount of vitamin B12